2011
DOI: 10.1068/p6835
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Preferences in the Size of Images of Real-World Objects

Abstract: Konkle and Oliva (in press, Journal of Experimental Psychology: Human Perception and Performance) found that the preferred ('canonical') visual size of a picture of an object within a frame is proportional to the logarithm of its known physical size. They used within-participants designs on several tasks, including having participants adjust the object's size to 'look best'. We examined visual size preference in 2AFC tasks with explicit aesthetic instructions to choose: "which of each pair you like best". We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 3 publications
4
18
0
Order By: Relevance
“…Consistent with this idea, a number of researchers have claimed that stored information about real-world size is represented in a perceptual or analog format (Moyer, 1973; Paivio, 1975; Rubinsten & Henik, 2002). Further, objects have a canonical visual size, proportional to the log of their familiar size, where smaller objects like alarm clocks are preferred at smaller visual sizes, and larger objects like horses are preferred at larger visual sizes (Konkle & Oliva, 2011; Linsen, Leyssen, Sammartino, & Palmer, 2011). On this more perceptual account of interference, in the congruent condition both objects have a better match to stored representations, which include visual size information, facilitating and/or interfering with visual size judgments.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, a number of researchers have claimed that stored information about real-world size is represented in a perceptual or analog format (Moyer, 1973; Paivio, 1975; Rubinsten & Henik, 2002). Further, objects have a canonical visual size, proportional to the log of their familiar size, where smaller objects like alarm clocks are preferred at smaller visual sizes, and larger objects like horses are preferred at larger visual sizes (Konkle & Oliva, 2011; Linsen, Leyssen, Sammartino, & Palmer, 2011). On this more perceptual account of interference, in the congruent condition both objects have a better match to stored representations, which include visual size information, facilitating and/or interfering with visual size judgments.…”
Section: Discussionmentioning
confidence: 99%
“…The canonical size effect was reported to be related to the real-world size of the stimulus objects (Konkle & Oliva, 2011;Linsen et al, 2011). However, it is unclear whether the objects in our stimulus would be included in this type of preference.…”
Section: Methodsmentioning
confidence: 90%
“…Our behavior is often influenced by aesthetic preferences. There are numerous studies on the relationship between visual aesthetic judgments and preferences with visual features such as color (Granger, 1955;Guilford & Smith, 1959;Hurlbert & Ling, 2007;McManus, Jones, & Cottrell, 1982;Palmer & Schloss, 2010), spatial frequency (Graham & Field, 2007;Graham & Redies, 2010), orientation (Latto & Russell-Duff, 2002), and size (Konkle & Oliva, 2011;Linsen, Leyssen, Sammartino, & Palmer, 2011). Such visual preferences often affect our behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reportedly, the size and color of an element object are responsible for giving some impression [6][7][8][9]. Furthermore, Stevanov et al showed that visual illusion has valence for aesthetic impressions [10].…”
Section: Introductionmentioning
confidence: 99%